Analisis Signifikansi Pengaruh Dividend Payout Ratio, Earning Per Share dan Debt to Equity Ratio terhadap Return Saham - Luh Putri Mas Mirayani; RR. Maria Yulia Dwi Rengganis; I Gusti Ayu Ratih Permata Dewi (Jurnal Inovasi Akuntansi (JIA), 2024)
This study examines the influence of Dividend Payout Ratio (DPR), Earning Per Share (EPS), and Debt to Equity Ratio (DER) on Stock Returns in companies listed on the LQ45 Index of the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Using a quantitative approach, this research analyzed data from annual financial reports of 22 companies selected through purposive sampling, with a total of 66 observations. Multiple linear regression analysis was employed to evaluate the relationships between variables. The results indicate that DPR and EPS have a positive and significant impact on Stock Returns, with respective p-values of 0.001. This suggests that higher dividends and improved financial performance significantly enhance stock returns. On the other hand, DER does not have a significant influence on Stock Returns. This study provides practical implications for companies to strengthen their dividend policies and financial performance to attract investors. Investors are recommended to use DPR and EPS as primary indicators in forming an optimal investment portfolio. The findings contribute to the theoretical literature on financial ratios and stock performance in developing markets and suggest opportunities for future research, including additional variables such as macroeconomic factors or market conditions, to enhance Stock Return prediction models.